IMPLEMENTASI ADAPTIF PENDIDIKAN KESETARAAN SEKOLAH MENENGAH ATAS UNTUK ANAK YANG BERKONFLIK DENGAN HUKUM: STUDI KUALITATIF DI PKBM ANAK CEMERLANG BENGKULU - Ena Anita; Viola Dian Sastra; Mutiara Velisa; Citra Lorenza; Hery Agusta (Journal Education for All: Media Informasi Ilmiah Bidang Pendidikan Luar Sekolah, 2025)
This study examines the implementation of a high school equivalency program (locally known as Package C in Indonesia) for Children in Conflict with the Law (CICL) at PKBM Anak Cemerlang in Bengkulu City. As part of non-formal education, the program is designed to provide flexible and inclusive learning opportunities for vulnerable learners. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation involving program managers, tutors, and participants. The findings reveal that learning is implemented through a combination of online instruction via WhatsApp and limited face-to-face mentoring, enabling flexibility in addressing participants’ legal constraints, psychological conditions, and socio-economic challenges. Supporting factors include strong tutor commitment, flexible instructional strategies, and a humanistic learning approach. However, major challenges remain, such as limited digital access, low digital literacy, unstable psychological conditions, and persistent social stigma. This study highlights the importance of adaptive and context-based learning models in non-formal education and contributes to the development of an inclusive educational framework that integrates flexibility, emotional support, and digital learning to ensure equitable access for marginalized youth.